Mughal Arcadia : Persian literature in an Indian court - Sharma, Sunil, 1964- (Harvard University Press, 2017)
This book is a study of the creation and demise of a poetic utopia at the Mughal court in early modern South Asia. The Mughals set up an empire in northern India in the early sixteenth century based on a Perso-Islamic model but ruled over an extremely diverse populace. In order to enhance their reputation in the Islamic world, the Mughals welcomed poets, artists, and scholars from different Persophone societies, many of whom migrated to India either to flee persecution or in search of better economic prospects. Poetry was central to all forms of courtly life at this time, giving poets a prestigious role, especially those who were native speakers of Persian, sometimes leading to tensions between émigré poets and local Indian ones. While the vibrant life in cities was the usual subject of topographical poetry, the apex of this cosmopolitan age was the court's preference for the valley of Kashmir as a setting for the practice of poetry, one that symbolized the idea of the empire as Arcadia. Due to several historical and political reasons, around the mid-seventeenth century the Mughal court lost its appeal as a refuge for literati, marking a major shift in the movement of individuals and the centers of Persian literary culture.--